Brief, Web‐based Education Improves Lay Rescuer Application of a Tourniquet to Control Life‐threatening Bleeding. Issue 2 (22nd March 2018) - Goolsby, Craig A.; Strauss‐Riggs, Kandra; Klimczak, Victoria; Gulley, Kelly; Rojas, Luis; Godar, Cassandra; Raiciulescu, Sorana; Kellermann, Arthur L.; Kirsch, Thomas D.
Abstract: Objective: The objective was to determine whether brief, Web‐based instruction several weeks prior to tourniquet application improves layperson success compared to utilizing just‐in‐time (JiT) instructions alone. Background: Stop the Bleed is a campaign to educate laypeople to stop life‐threatening hemorrhage. It is based on U.S. military experience with lifesaving tourniquet use. While previous research shows simple JiT instructions boost laypeople's success with tourniquet application, the optimal approach to educate the public is not yet known. Methods: This is a prospective, nonblinded, randomized study. Layperson participants from the Washington, DC, area were randomized into: 1) an experimental group that received preexposure education using a website and 2) a control group that did not receive preexposure education. Both groups received JiT instructions. The primary outcome was the proportion of subjects that successfully applied a tourniquet to a simulated amputation. Secondary outcomes included mean time to application, mean placement position, ability to distinguish bleeding requiring a tourniquet from bleeding requiring direct pressure only, and self‐reported comfort and willingness to apply a tourniquet. Results: Participants in the preexposure group applied tourniquets successfully 75% of the time compared to 50% success for participants with JiT alone (p < 0.05, risk ratio = 1.48, 95% confidence interval = 1.21–1.82). Participants place tourniquets in a timely fashion, are willing to use them, and can recognize wounds requiring tourniquets. Conclusions: Brief, Web‐based training, combined with JiT education, may help as many as 75% of laypeople properly apply a tourniquet. These findings suggest that this approach may help teach the public to Stop the Bleed.